Development of biocompatible and fully bioabsorbable PLA/Mg films for tissue regeneration applications. (15th October 2019) - Ferrández-Montero, A.; Lieblich, M.; González-Carrasco, J.L.; Benavente, R.; Lorenzo, V.; Detsch, R.; Boccaccini, A.R.; Ferrari, B.
Graphical abstract: Abstract: During recent years, Mg reinforced polylactic acid (PLA) composites have emerged as potential biocompatible and bioabsorbable materials for biomedical applications. It has been shown that Mg particles added to a matrix based on a biodegradable polymer can address the lack of bioactivity and the low mechanical properties of the polymers and, furthermore, it can counteract the detrimental effects associated to the high degradation rate of Mg, as alkalinization and elevated H2 release. Additionally, the polymer can protect the Mg particles, by tailoring their degradation rate. Former processing of these composites performed by extrusion, compression and injection molding employed Mg contents up to 10 wt%. Higher amounts of Mg resulted in heterogeneous materials and thermally degraded matrices, with the corresponding higher degradation rate. In the present work, Mg reinforced PLA films with Mg content as high as 50 wt% were obtained without compromising the thermal stability of the polymer. Firstly, a successful dispersion of Mg microparticles was achieved by a breakthrough in processing introducing a colloidal step where organic additives were added to modify the Mg particle surface and promote a chemically stable suspension. The resulting colloidal suspension was then used as feedstock to obtain composite films by tape casting. The films show advantageous in vitro behaviour in terms of degradation, hydrogen release and oxygen permeability. In addition, the viability with fibroblast cells (MEF) opens a window of opportunity for these composite films as bioabsorbable material for tissue engineering and wound dressing applications. Statement of Significance: Magnesium materials have extraordinary biodegradable properties and bioactive behavior due to release of Mg 2+ ions, which offer a promising opportunity for their applicability as biomaterials for tissue regeneration. However, Mg is one of the most reactive metals with a high degradation rate. In contact with water produces H2, associated with a risk of failure of the implant. One alternative to minimize this drawback is the use of Mg particles surrounded by a biodegradable biocompatible polymer such as polylactic acid (PLA) to obtain PLA/Mg composites. In this work we processed Mg reinforced PLA in the shape of films that would be suitable for tissue regeneration. In vitro behavior of PLA/Mg films demonstrated that Mg 2+ ions increase the fibroblast cells growth.